Incidence if Plasmodium Falciparum Malaria in Querecotillo, Sullana, Peru - 1997 - Bellina, Cecilia (1999)
OBJECTIVE: To determine the incidence of Plasmodium falciparum malaria in Querecotillo, an area with a course of increasing prevalence rates for this disease. MATERIAL AND METHODS: Information consigned at the 1997 Book of Record and Following of Malaria Patients, was analyzed. RESULTS: Ages ranged predominantly between 15 and 44 years (69,6% of cases). Incidence rate was 14,2%; and the villages of Peña, Puente, Victoria and Querecotillo had the highest prevalence rates. Population in able-to-work ages was the most affected, and the peak incidence was during May, June and July. CONCLUSIONS: Querecotillo is a high risk area for Plasmodium falciparum malaria, and there are economic, social, cultural and weather factors which exerts influence on disease statistics.